Liquidity Ratio Analysis for Evaluating Corporate Financial Performance: Evidence from PT Charoen Pokphand Indonesia Tbk Listed on the Indonesia Stock Exchange - Hasibuan, Risma Khoir; Ramadhani, Laily; Nasution, Hafni Cholida (Global Insights in Management and Economic Research, 2026)
Purpose of the study: This study aims to evaluate the financial performance of PT. Charoen Pokphand Indonesia, Tbk during the period 2019-2023 based on liquidity ratios, specifically Current Ratio, Quick Ratio, and Cash Ratio. The research seeks to determine whether the company maintains adequate liquidity to meet short-term obligations and sustain operational efficiency. Materials and methods: This study employs a descriptive qualitative research design utilizing secondary data obtained from the audited annual financial statements of PT. Charoen Pokphand Indonesia, Tbk. The population comprises all financial reports of the company, with the sample consisting of five consecutive years of financial statements (2019-2023). Data analysis was conducted through liquidity ratio calculations and comparison against industry standard benchmarks. The analytical framework follows established financial ratio analysis methodologies as documented in contemporary accounting literature. Results: The findings reveal that PT. Charoen Pokphand Indonesia, Tbk demonstrates varying levels of liquidity performance across the three measured ratios. The Current Ratio achieved an average of 209%, exceeding the industry standard of 200%, indicating satisfactory short-term debt coverage capacity. However, the Quick Ratio averaged 112%, falling below the industry benchmark of 150%, suggesting potential challenges in meeting immediate obligations without inventory liquidation. Similarly, the Cash Ratio averaged 29%, significantly below the industry standard of 50%, indicating limited cash reserves relative to current liabilities. Conclusions: The study concludes that while PT. Charoen Pokphand Indonesia, Tbk maintains adequate overall liquidity as measured by the Current Ratio, the company exhibits suboptimal performance in more stringent liquidity measures. The declining trend in Quick Ratio and Cash Ratio over the five-year period warrants strategic attention to enhance cash management practices and reduce dependency on inventory for short-term obligation fulfillment.